1998
DOI: 10.1143/jjap.37.4649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Contamination on Thin Gate Oxide Quality

Abstract: The impact of organic contamination on the quality of 5-nm-thick gate oxide structures, both before and after gate oxidation, is studied. Sources of organic contamination are chemical surface modification (i.e. hexamethyldisilazane priming), wafer box storage and extended vacuum exposure. Gate oxide integrity is evaluated electrically. The origin and/or nature of the organic contamination is seen to have different effects on the electrical breakdown. Care should be taken when exposing sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…It has been reported that surfaces exposed to vacuum conditions are prone to organic contamination pickup compared with surfaces stored in a wafer box. [7] Therefore, the primary cause of contact angle increase in our study was exposure to the vacuum environment of the SIMS chamber. A quick effective SIMS measurement is essential to minimise changes in the surface chemistry and accumulated contamination within the SIMS instrument.…”
Section: Resultsmentioning
confidence: 90%
“…It has been reported that surfaces exposed to vacuum conditions are prone to organic contamination pickup compared with surfaces stored in a wafer box. [7] Therefore, the primary cause of contact angle increase in our study was exposure to the vacuum environment of the SIMS chamber. A quick effective SIMS measurement is essential to minimise changes in the surface chemistry and accumulated contamination within the SIMS instrument.…”
Section: Resultsmentioning
confidence: 90%
“…Various kinds of chemical compounds existing in the ambient atmosphere, such as acids, bases, organic compounds, inorganic compounds, and metals, can adsorb at the material surface [1][2][3][4][5][6][7][8]. This potentially multiple-component contamination is a fundamental problem in many industrial processes that use or produce highly clean surfaces, such as wet cleaning, lithography, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples in literature indicate also the possible effects that organic and silicon based contaminants can have on IC processes. At the wafer level these kinds of molecules may form a nanometric layer on the surface affecting gate oxide Time Zero Dielectric Breakdown (TZBD) reliability [4][5][6] as well as thickness ellipsometry and/or reflectometry measurements [7]. During lithography processes it has been widely reported that organics and silicon based compounds may condense on lenses, causing "hazing"; further their presence in the laser light path between the lens and substrate can result in poor optical transmission and laser throughput [8][9].…”
Section: Introductionmentioning
confidence: 99%